2009
DOI: 10.1038/aja.2008.38
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and identification of apolipoprotein C-I in hormone-refractory prostate cancer using surface-enhanced laser desorption/ionization time-of-flight mass spectrometry

Abstract: Androgens play a central role in prostate cancer pathogenesis, and hence most of the patients respond to androgen deprivation therapies. However, patients tend to relapse with aggressive prostate cancer, which has been termed as hormone refractory. To identify the proteins that mediate progression to the hormone-refractory state, we used protein-chip technology for mass profiling of patients' sera. This study included 16 patients with metastatic hormone-refractory prostate cancer who were initially treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…, in our study, high levels of both apolipoprotein A‐I and apolipoprotein A‐II were found in the cancerous cell region in prostate cancer, in contrast with the previous study . Apolipoprotein C‐I has also been shown to be a potential biomarker for prostate cancer with high expression levels in serum based on surface‐enhanced LDI‐TOF MS and immunohistochemical analysis, which is consistent with our MALDI‐MSI study (Fig. B), where the peptide at m / z 6633.1 (apolipoprotein C‐I) was mainly distributed in the cancerous region of the tissue.…”
Section: Resultssupporting
confidence: 91%
“…, in our study, high levels of both apolipoprotein A‐I and apolipoprotein A‐II were found in the cancerous cell region in prostate cancer, in contrast with the previous study . Apolipoprotein C‐I has also been shown to be a potential biomarker for prostate cancer with high expression levels in serum based on surface‐enhanced LDI‐TOF MS and immunohistochemical analysis, which is consistent with our MALDI‐MSI study (Fig. B), where the peptide at m / z 6633.1 (apolipoprotein C‐I) was mainly distributed in the cancerous region of the tissue.…”
Section: Resultssupporting
confidence: 91%
“…It is secreted by the liver and is mainly distributed on the surface of very low density lipoprotein (VLDL), chylomicrons (CM) and high density lipoprotein (HDL) [ 14 ]. At present, APO C-I is a potential serum marker for colorectal cancer [ 15 ], prostate cancer [ 16 ], breast cancer [ 17 ], lung cancer [ 18 ], papillary thyroid carcinoma [ 19 ], malignant pleural mesothelioma [ 20 ], and liver fibrosis [ 21 ]. It has also been suggested as a potential serum marker for gastric cancer [ 22 ], which may be related to the regulation of its gene expression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…1). According to Polanski's compilation [17] and other recent references [21][22][23][24][25][26][27][28][29][30][31][32][33], there are 14 proteins in the panel that have been linked to multiple types of cancer. For instance, serum paraoxonase/arylesterase 1 has been observed to be downregulated in patients with gastric [34] and pancreatic [35] cancers.…”
Section: Protein and Peptide Selectionmentioning
confidence: 99%